Os distúrbios osteomusculares e suas consequências para os profissionais da odontologia - Freire, Ana Carolina da Graça Fagundes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Dentistry is a job very vulnerable to occupational risks mainly those concerning work postures. Objective: To verify the prevalence of musculoskeletal disturbs in dentists who are enrolled in post-graduation courses in many specialties, stablishing possible relation with social, demographic and occupational factors; to evaluate the professionals' perception regarding risk factors and correlation the musculoskeletal pain to the consequent incapacity among dental professionals. Method: In this cross-sectional study the professionals answered to the validated instruments: Work-related activities that may contribute to job - related pain and/or injury, Nordic Musculoskeletal Questionnaire (NMQ), Pain Disability Questionnaire (PDQ) and the Numerical Scale for Pain. Variables about social, demographic and occupational characterization were also collected. The data analysis was performed using SPSS software - version 21.0 and it was applied the Sperman's Test. To compare the groups it was applied the non-parametric Mann-Whitney and Kruskal-Walis tests. Results: of total (N=94), 90.4% reported that they have experience of musculoskeletal pain, and these dentists showed risk 13.40 times higher to feel pain in inferior part of back than those who had no symptoms. The most prevalent areas of pain were the neck (58.5%), inferior (57.4%) and superior (55.3%) parts of back, shoulders (46.8%), and fists/hands (44.7%). The relation between the existence of pain and uncomfortable occupational postures of dentists was statistically significant, e.g. to work in wrong positions or in strait locals (p-value 0.005). Total average of PDQ was 7.91; on functional condition domain (FC) ...

A odontologia é uma profissão muito vulnerável a riscos ocupacionais, principalmente os relacionados à postura de trabalho. Objetivo: Verificar a prevalência dos distúrbios osteomusculares em cirurgiões-dentistas que frequentaram cursos de pós-graduação de diversas especialidades, estabelecendo possíveis relações com fatores sociodemográficos e ocupacionais, avaliar a percepção dos profissionais em relação aos fatores de risco e correlacionar a dor osteomuscular com a incapacidade funcional experimentada pelos profissionais da odontologia. Metodologia: trata-se de um estudo transversal, no qual os profissionais responderam aos instrumentos validados: Work-related activities that may contribute to job- related pain and/or injury, NMQ Nordic Musculoskeletal Questionnaire, Pain Disability Questionnaire (PDQ) e a Escala Numérica da Dor. Foram, ainda, coletadas variáveis de caracterização sociodemográfica e ocupacional. A análise dos resultados foi realizada através do programa SPSS - versão 21.0, e utilizou-se o teste de correlação de Spearman. Para comparação de grupos foram utilizados os testes não paramétricos de Mann Whitney e Kruskal-Wallis. Resultados: Do total de cirurgiões dentistas entrevistados (N=94), 90.4% relataram ter experiência de dor osteomusculares e apresentaram risco de dor na região inferior das costas 13.40 vezes maior do que os sujeitos assintomáticos. As regiões mais prevalentes foram: pescoço (58.5%), parte inferior (57.4%) e superior das costas (55.3%), ombros (46.8%) e punhos/mãos (44.7%). Observou-se significância estatística em relação à presença de dor quando o cirurgião dentista encontra-se numa situação ocupacional desconfortável, como por exemplo, trabalhar em posições incorretas ou em locais muito apertados (p-valor 0.005). A média total do PDQ foi de 7.91, para o domínio condição funcional (CF)...
Keywords: Odontologia; Transtorno do desenvolvimento da coordenação; Ergonomia; Dor; Saúde do trabalhador; Fatores de risco; Deficientes; Lesões por esforços repetitivos